Práticas de letramentos críticos : repensando a aula de língua inglesa no ensino médio, um estudo de caso no IFMT - Penteado, Rita de Cássia dos Santos (2018)
Considering the current context of English language teaching in the public school, the use of technologies and lecture opportunities based on critical literacy theory, it is necessary to understand how these items relate and what consequences they can bring together for learning, when combined with a pedagogical practice that contributes to relevant and meaningful learning. This scenario took place with students dealing with their cultural and linguistic differences and with me, an advisor, rediscovering myself when facing my difficulties along the way. Based on this premise, this paper discusses a high school experience with a group of students who participated in an English language teaching and learning proposal, using research and production of documentary in English. Through this proposal, the students were able to experience learning situations by avoiding conventional didactic material, and also, having the opportunity of reflexivity during it. Theoretically, this study is based on the perspectives of critical literacy, based on studies by Menezes de Souza & Monte-Mór (2006), Jordão and Fogaça (2007), Jordão (2010), Mattos (2015), with emphasis on reflexivity, criticality, that could be awakened in the students, and the gaps by at the Duboc (2015). The theoretical methodological approach used was collaborative actionresearch, based on Denzin and Lincoln (2010), Bortoni-Ricardo (2013) and Zeichiner (2001). Through diaries, questionnaires and the analysis of my own practices, I was able to understand the datas generated. In the results there are evidences that signal the occurrence of reflexivity and criticality processes, based on the theoretical perspectives addressed, to different degrees of complexity.